AUDIT SISKOHAT MENGGUNAKAN FRAMEWORK COBIT PADA DOMAIN DELIVER AND SUPPORT (DS) DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Tri Widayanti (STMIK PONTIANAK, 2012)
ABSTRACT : Auditing of Integrated Hajj Computerized System in the Ministry of Religious Affairs Office of the Yogyakarta Special Province implemented using the COBIT framework for organizing the procession of pilgrims. Audits performed by the method of interviews and questionnaires, which refers to the COBIT framework as a standard. The questionnaire was made in two types of questionnaires I Preliminary Survey to determine the IT processes to be selected and maturity level II questionnaire to measure the level of maturity. Preliminary analysis of the survey have managed to pick some of the IT processes that have been carried out on one of the Office of the Province of DIY religious ministries. The IT processes are selected domain DS include DS5, DS10, DS11, DS12, and DS13. Based on the results of calculation of maturity values can be in the know that for the DS10, DS11 and DS13 has a maturity value respectively 3.05, 3.16, and 3.13 which means the process defined at the level which is a process conducted regularly in accordance with a standard formal written. While the maturity values for process DS5 and DS12 may have a maturity value respectively 2.72 and 2.84, which means is at repeatable but intuitive level the process is done on a regular basis but you are not formal rules and guidelines. The results of this study indicate that for the overall process maturity level selected is between levels 2 and 3, so it can be concluded that SISKOHAT has been implemented in accordance with the procedures, communicated and some have been documented. Keywords: Integrated Hajj Computerized System, audit, COBIT